Release of selected amino acids from zinc carriers - Dyja Renata; Dolińska Barbara; Ryszka Florian (Acta Pharmaceutica)
The paper deals with the results of an investigation of the release of selected amino acids (histidine, tryptophan, tyrosine) from model suspensions prepared by co-precipitation with zinc chloride. It has been proven that the influence of the Zn(II)/amino acid molar ratio on dissolution profiles of the tested amino acids and dissolution half-life (t1/2) of histidine or tryptophan is significant. The amount of amino acid in the dispersed phase (supporting dose) is a determinant of the amino acid release profile. There is a minimal supporting dose (30.0 μmol of histidine or 17.4 μmol of tryptophan) that provides release of similar amounts of amino acid (4.1–4.6 μmol of histidine or 8.7–9.9 μmol of tryptophan) after the same time intervals. The tyrosine release profiles follow first order kinetics since the supporting dose (0.9–11.2 μmol) is limited by the tyrosine low solubility in water.